Bilateral Axillary Accessory Breast Resection in a Young Woman: Case Report And Literature Review - Ana Gabriela Suárez Hidalgo; Natasha Ham Rodríguez; Mitzi Fernández Luna (International Journal of Medical Science and Clinical Research Studies, 2026)
Introduction: Accessory breast tissue, or ectopic breast tissue, is a rare congenital anomaly resulting from incomplete involution of the embryonic mammary ridge. Although it is usually asymptomatic, it may become clinically apparent during periods of hormonal stimulation, presenting with pain, enlargement, functional limitation, and aesthetic or psychological distress. The axillary region is one of the most common locations. Case presentation: We present the case of a 20-year-old female patient with a history of bilateral accessory breast tissue present since the early stages of development. During the six months prior to consultation, she experienced progressive and cyclical enlargement of the axillary tissue, associated with mild pain, functional limitation of the upper extremities, and a significant impact on self-esteem and body image. Physical examination revealed bilateral axillary accessory breasts, classified as Kajava type I on the right and type II on the left. Bilateral breast and axillary ultrasound showed ectopic glandular tissue without evidence of malignancy and was classified as BI-RADS 2. Bilateral mastectomy of the accessory breasts was performed by direct excision through elliptical incisions under anesthetic sedation. Histopathological examination confirmed benign breast glandular tissue without atypia or malignancy. The postoperative course was satisfactory, with no immediate or late complications. At the one-month follow-up, adequate wound healing, absence of seroma, hematoma, or infection, complete recovery of mobility of both upper extremities, and significant improvement in the patient’s self-esteem, body image, and aesthetic satisfaction were observed. Conclusions: Bilateral accessory breast tissue should be considered in the differential diagnosis of axillary masses in young women. Clinical evaluation complemented by imaging studies allows for accurate diagnosis and exclusion of malignant disease. In symptomatic patients, surgical resection is a safe and effective therapeutic option associated with functional, aesthetic, and psychological improvement. This case contributes to the clinical recognition and comprehensive management of an uncommon condition whose impact on quality of life is often underestimated.